Molecular Design Strategies for Electrochemical Behavior of Aromatic Carbonyl Compounds in Organic and Aqueous Electrolytes. Issue 17 (25th July 2019) - Peng, Huiling; Yu, Qianchuan; Wang, Shengping; Kim, Jeonghun; Rowan, Alan E.; Nanjundan, Ashok Kumar; Yamauchi, Yusuke; Yu, Jingxian
Abstract: To sustainably satisfy the growing demand for energy, organic carbonyl compounds (OCCs) are being widely studied as electrode active materials for batteries owing to their high capacity, flexible structure, low cost, environmental friendliness, renewability, and universal applicability. However, their high solubility in electrolytes, limited active sites, and low conductivity are obstacles in increasing their usage. Here, the nucleophilic addition reaction of aromatic carbonyl compounds (ACCs) is first used to explain the electrochemical behavior of carbonyl compounds during charge–discharge, and the relationship of the molecular structure and electrochemical properties of ACCs are discussed. Strategies for molecular structure modifications to improve the performance of ACCs, i.e., the capacity density, cycle life, rate performance, and voltage of the discharge platform, are also elaborated. ACCs, as electrode active materials in aqueous solutions, will become a future research hotspot. ACCs will inevitably become sustainable green materials for batteries with high capacity density and high power density. Abstract : To achieve an excellent electrochemical performance, under the premise of clarifying the relationship of the molecular structure and electrochemical properties, the adjusting strategies for molecular structure of aromatic carbonyl compounds for improving solubility, electronic conductivity, and electrochemical activity are given. In addition, the electrochemical behavior of aromatic carbonyl compounds is explained with the nucleophilic addition reaction.